1998
DOI: 10.1161/01.cir.97.6.581
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Thrombin Inhibition Reduces Restenosis After Balloon Angioplasty in Porcine Coronary Arteries

Abstract: Background-Arterial injury after percutaneous transluminal coronary angioplasty (PTCA) triggers acute thrombus formation and thrombin generation. Hirudin, a potent and direct thrombin inhibitor, prevents thrombus formation after arterial injury. Two large clinical trials showed marked reduction in acute clinical events but no long-term benefits in reducing restenosis during short-term administration of thrombin inhibitors. Our hypothesis is that adequate, maintained thrombin inhibition, by inhibiting all the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 55 publications
2
34
0
3
Order By: Relevance
“…No description on the start time of hirudin treatment related to angioplasty. Results from more recent studies in atherosclerotic rabbits or pigs indicated prolonged infusion of hirudin for 2 weeks or early start plus delayed infusion of hirudin (second infusion at 24 h after angioplasty) significantly reduced angioplasty-induced restenosis [7, 8]. Those findings suggest that hirudin infusion potentially reduces angioplasty-induced restenosis through the modification of regimens.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No description on the start time of hirudin treatment related to angioplasty. Results from more recent studies in atherosclerotic rabbits or pigs indicated prolonged infusion of hirudin for 2 weeks or early start plus delayed infusion of hirudin (second infusion at 24 h after angioplasty) significantly reduced angioplasty-induced restenosis [7, 8]. Those findings suggest that hirudin infusion potentially reduces angioplasty-induced restenosis through the modification of regimens.…”
Section: Discussionmentioning
confidence: 98%
“…Hirudin treatment reduced early cardiac events but did not bring long-term benefit to post-angioplasty patients [6]. Recent studies indicated that prolonged or early started infusion of hirudin may considerably reduce restenosis in experimental animal vascular injury models [7, 8]. Results from large-scale clinical trials indicated that hirudin treatment causes significantly higher incidence of intracranial or other major bleeding complications compared to conventional heparin treatment [9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…A long-term beneficial effect of thrombin inhibitors on restenosis has not been shown in humans [5, 6]. Recent studies demonstrated that the modification of the administration of hirudin through early and/or prolonged infusions substantially improved its preventive effects on the development of restenosis in experimental animal models [7, 8]. Results of phase III clinical trials indicated that hirudin significantly increased the frequency of intracerebral or major hemorrhage [9]which limits its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…First, the mechanism by which new thrombi or newly injured vessels which are very thrombogenic become less so with time, a process known as "passivation" (50,51). The ability of phospholipid oxidation, a time-dependent process, to enhance APC anticoagulant function would be expected to contribute to this process.…”
Section: Discussionmentioning
confidence: 99%